The role of Latin America medicinal plants in wound healing - Sánchez-Ramos, Mariana; Ruiz-Betancourt, Andrea; Tadeo-Cuenca, Stephany Abigail; Román-Guerrero, Angélica; Columba-Palomares, María Crystal; Guerrero-Alonso, Araceli; Bernabé-Antonio, Antonio; Ojeda-Ramírez, Deyanira; Cruz-Sosa, Francisco (Frontiers in Chemical Engineering, 2025)
Wound healing represents a global public health problem when it is not treated correctly, which can cause complications for the patient, such as functional loss of an organ, amputation, and even death. At a biological level, wound healing involves a complex mechanism in which the immune system and cellular biochemical cascades intervene in a coordinated manner, whose development occurs in stages such as inflammation, proliferation, and remodeling. Therefore, therapies have been developed to accelerate wound healing and have proven effective. However, factors such as diabetes mellitus limit the healing process because it causes alterations in microvascular dysfunction, as well as in the inflammatory response and greater oxidative stress. This is reflected in an abnormal healing process; therefore, the search for healing compounds has become an area of interest. In this regard, medicinal plants have been used for centuries to treat wounds in different cultures in the world. Hence, this review documents the main plant species used in Latin America due to its great biodiversity and numerous species that are potentially important for the development of new active healing compounds. In this review, 62 plant families with wound healing studies were found, highlighting Fabaceae, Asteraceae and Euphorbiaceae family. Additionally, 32 natural compounds with diverse structural nature were found, whose effects have been evaluated in in vivo and in vitro models, which are essential for studying the pathogenesis of the tissue repair mechanism, detecting new biomarkers, and evaluate new treatments. Currently, several models are used to study the wound healing process, including in silico, in vitro, and in vivo models. On the other hand, there is no appropriate model to determine the wound healing effect, and, in many cases, they are combined to provide sufficient scientific evidence. Therefore, this review demonstrates that Latin America is a potential region for research into sources of healing molecules. Nevertheless, other species are still being studied whose scientific findings allow generating viable alternatives for the solution of health problems associated with wound healing.